Robust Image Zero- Watermarking Based on Complex Zernike Moment - Khalid, Edris; Fakhreldin, Mohammed Adam Ibrahim; Jasni, Mohamad Zain; Tuty Asmawaty, Abdul Kadir (2014)
This paper proposes a robust zero-watermarking algorithm based on Complex Zernike moment to resist various signal processing operations and geometric transformations. Zero watermarking algorithm changes the operation method of embedding watermark in the original data. Instead, it employs the significant characteristics of the original data to construct watermarking information to successfully avoid the contradiction between robustness and invisibility and increase the robustness of the watermarking. First, perform displacement and scaling standardization process for the tested image, then calculate the Complex Zemike Moment argument of the standardized image to get an argument value; after binarization of the argument value, construct the feature image regarded as watermarking. Experimental results show that the proposed method has strong robustness to various attacks specially geometric attacks.